2021
DOI: 10.1108/ecam-05-2021-0436
|View full text |Cite
|
Sign up to set email alerts
|

Influence of practitioners' characteristics on risk assessment in Green Building projects in emerging economies: a case of Vietnam

Abstract: PurposeRisks are considered a significant obstacle to Green Building (GB) development and have recently received significant attention from both construction practitioners and academics. This study aimed to identify critical GB risks and explore the relationship between participants' characteristics and risk assessment.Design/methodology/approachFirstly, a list of GB risks was developed based on a comprehensive literature review and interviewing GB experts. After that, a survey of 207 construction professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
(92 reference statements)
2
9
0
Order By: Relevance
“…This finding provides insight and could help practitioners develop a suitable strategy to deal with this factor in implementing GB projects. This result aligns with the research of Nguyen et al (2021), who rated this risk factor as the most critical risk factor. Indeed, this problem could restrain the development of GBs; thus, enhancing owners' awareness and knowledge could mitigate this risk (Nguyen et al, 2021).…”
Section: The Most Critical Risk Factorssupporting
confidence: 91%
See 4 more Smart Citations
“…This finding provides insight and could help practitioners develop a suitable strategy to deal with this factor in implementing GB projects. This result aligns with the research of Nguyen et al (2021), who rated this risk factor as the most critical risk factor. Indeed, this problem could restrain the development of GBs; thus, enhancing owners' awareness and knowledge could mitigate this risk (Nguyen et al, 2021).…”
Section: The Most Critical Risk Factorssupporting
confidence: 91%
“…The most critical risk factor is HD4, which relates to GB designers' lack of experience. This indicates that the incapacity of GB designers is a major problem in the design phase of GB projects in Vietnam (Nguyen et al, 2021). This research also revealed that this risk factor has the greatest impact (impact level ranked first) and is a common problem in Vietnam (probability of occurrence ranked third).…”
Section: The Most Critical Risk Factorsmentioning
confidence: 67%
See 3 more Smart Citations